1996
DOI: 10.1080/10556799608205454
|View full text |Cite
|
Sign up to set email alerts
|

Brightest star cluster candidates in eight late-type galaxies of the local complex

Abstract: The magnitudes and colon of 48 star cluster candidates in the galaxies NGC 1560, IC 10, UGCA 86, UGCA 105, DDO 165, Ho I, Ho I1 and Ho 1X are obtained from the plates taken at the 6-m telescope. From 3 to 11 such objects are found in each galaxy. The distribution of all cluster candidates on the color -absolute magnitude diagram is close to the distribution of the LMC clusters. Depending on the luminosity, three groups of objects are distinguished -very bright, bright and of intermediate brightness. Their abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 6 publications
0
17
1
Order By: Relevance
“…17. Three brightest blue supergiant candidates, #34, 40, and 35 in Table 14, give us a distance modulus of 29.08, which is lower than the estimate µ 0 (3B) = 29.51 derived by Georgiev et al (1997). We have not found red stars in this galaxy.…”
Section: Distance Estimatescontrasting
confidence: 39%
“…17. Three brightest blue supergiant candidates, #34, 40, and 35 in Table 14, give us a distance modulus of 29.08, which is lower than the estimate µ 0 (3B) = 29.51 derived by Georgiev et al (1997). We have not found red stars in this galaxy.…”
Section: Distance Estimatescontrasting
confidence: 39%
“…5 and 4. 5, but for our purposes the images were Makarova et al (1997Makarova et al ( , 1998 1, 4 , Tikhonov & Karachentsev (1998) 2 and Georgiev et al (1997) 3 . A gallery of our images is shown in Fig.…”
Section: Sample and Imagingmentioning
confidence: 99%
“…Accurate distances are becoming available as photometric distance determinations 1 (Makarova et al 1997;Georgiev et al 1997;Tikhonov & Karachentsev 1998;Makarova et al 1998;Karachentsev & Drozdovsky 1998). The combination of distance information and photometry will enable a thorough study of the photometric parameters of these systems.…”
Section: Introductionmentioning
confidence: 99%
“…(Karachentsev & Tikhonov 1993) pointed out seven candidates for star clusters in IC 10 and (Georgiev et al 1996) provided photometric data on them. Based on HST ACS/WFC images, we checked these possible clusters and found that four of them are actually star clusters, while three probable clusters are outside the available HST images.…”
Section: Star Clustersmentioning
confidence: 99%